Defects of democracy: The continuity of identity politics in post-reform regional elections - Danugroho, Agus (Jurnal Sosiologi Dialektika, 2024)
Identity politics in Indonesia is more closely related to issues of race, religion, ideology and local interests than other issues. This research aims to determine the impact of identity politics in every regional election (pilkada) in Indonesia. There are various ways in winning regional election (pilkada) strategies used by each candidate, one of which is the use of identity politics. Identity politics is a sign of the flaws in the nation’s democracy that has been built since the reform was initiated. There are still many political elites who still preserve their political identity, hampering democratic development. This research is a qualitative descriptive study with arguments built from facts and supported by secondary sources. The results of this research found that in the regional elections (pilkada) in several regions, it was proven that political identities were still visible, such as politicizing religion and certain ethnic symbols, which were involved in the victory of one of the candidates. Apart from that, this research also explains the history of democracy that has occurred in regional elections (pilkada), showing the political identities that still exist in them. This study concludes that one of the impacts of identity politics is the erosion of national unity which results in the Indonesian nation’s national resilience faltering.